A coupled modelling framework to assess the hydroecological impact of climate change. (April 2019) - Visser, Annie Gallagher; Beevers, Lindsay; Patidar, Sandhya
Abstract: Rivers are among the ecosystems most sensitive to climate change. Whilst methods quantifying the impact and uncertainty of climate change on flow regime are well-established, the impact on hydroecological response is not well understood. Typically, investigative methods are qualitative in nature or follow quantitative methods of limited scope, whilst the effect of uncertainty is frequently minimised. This paper proposes a coupled hydrological and hydroecological modelling framework to assess the impact of climate change on hydroecological response quantitatively. The characterisation and reduction of modelling uncertainties was critical to the development of the framework. The ability of the framework is illustrated through application to a case study river, the River Nar, Norfolk, England, using the UKCP09 probabilistic climate projections (high emissions scenario, SRES A1F1). The results show that, by the 2050s, a reduction in instream biodiversity is virtually certain if future emissions follow the assumptions of SRES A1F1. Disruption to the natural low flow processes, essential to ecosystem functioning, is also indicated. These findings highlight the importance of the framework in water resources adaptation, particularly with respect to future environmental flows management. Highlights: We propose a modelling framework to assess hydroecological response to climate change. Characterisation and reduction of uncertainty considered throughout. Provides quantifiable measure of the uncertainty in the hydroecological projections. Case study sees reduced instream biodiversity and disruption to flow processes.